2005
DOI: 10.1093/ps/84.9.1383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary oligochitosan supplementation on ileal digestibility of nutrients and performance in broilers

Abstract: The effect of dietary chitosan oligosaccharides (COS) supplementation on ileal digestibilities of nutrients and performance in broilers was assessed by feeding graded levels (0, 50, 100, 150 mg/kg) of COS. Two thousand four hundred male commercial Avian broilers (1-d-old) were assigned randomly to 5 dietary treatment groups (60 birds per pen with 8 pens per treatment). Diet A was a typical corn- and soybean meal-based diet supplemented with 6 mg/kg of an antibiotic flavomycin (positive control). Diet B was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 136 publications
(101 citation statements)
references
References 11 publications
6
87
0
8
Order By: Relevance
“…15 Our recent studies with the same birds as in this study showed that dietary supplementation of oligochitosan (COS) increased the ileal digestibility of nutrient and improved performance in broilers. 16 We have also reported that dietary supplementation of COS to weanling piglets promoted intestinal microflora balance and enhanced immune function. 12 At present, little is known about the effect of chitosan on the development of avian lymphoid organs or the molecular mechanisms of its action on the immune response.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…15 Our recent studies with the same birds as in this study showed that dietary supplementation of oligochitosan (COS) increased the ileal digestibility of nutrient and improved performance in broilers. 16 We have also reported that dietary supplementation of COS to weanling piglets promoted intestinal microflora balance and enhanced immune function. 12 At present, little is known about the effect of chitosan on the development of avian lymphoid organs or the molecular mechanisms of its action on the immune response.…”
Section: Introductionmentioning
confidence: 83%
“…It is tacitally assumed that the supplementation of such compounds to food-animal diets can minimise the use of antibiotics, thereby reducing the possible occurrence of drug resistance in bacteria. 3 To better understand the mechanisms for the beneficial action of COS on immune functions, we determined the effects of COS on lymphoid organ development, serum concentrations of IgG, IgA and IgM, and cell mRNA expression of IL-6 and IL-1β (the present study) 16 in chicks. Results of this study showed that chicks supplemented with 100 or 150 mg kg −1 COS had heavier weights of immune organs, and higher serum levels of immunoglobulins, which collectively suggest an improvement in the immune response.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations